Evaluasi Pelayanan Kesehatan Jiwa Berbasis Komunitas Di Kota Palembang - Ririn Noviyanti Putri; Haerawati Idris; Nur Alam Fajar (Universitas Batanghari Jambi, 2020)
The concept of complete mental health efforts is the handling of health problems and its foundation includes community mental health efforts, supported by basic mental health services and strengthened integrated referral mental health services. Most of ODGJ have not gotten health care. Not yet optimal mental health services indirectly affect the success rate of health development. This research aims to analyse the implementation of community-based mental health services in Palembang. Methods of research with qualitative design, informant in the research is chosen purposive. Data retrieval techniques with in-depth interviews to 12 informant, observation and study of documents. Triangulation is done in the form of triangulation of source, method and data. Results showed that the low public awareness of mental health is still low because of the high level of negative stigma of society and low public knowledge that can impact on the support that will be provided by Family. So the empowerment of community needs to reach people to access mental health services. This research suggests that there is a proactive stance from the public health center to reach people throughout their workforce by reproducing activities outside the public health center, strengthening cross-sector cooperation and empowering community.